THE PARTITION DIMENSION OF CYCLE BOOKS GRAPH B_(m,n) WITH A COMMON PATH P_2 - Santoso, Jaya; Darmaji, Darmaji (PATTIMURA UNIVERSITY, 2025)
Suppose is a connected graph with elements of a set of vertices denoted by and a subset of . The distance between and is the shortest distance to every vertex in . Let be a partition of , where each subset belongs to . The representation of a vertex with respect to is defined as the set of distances from to each vertex in . If each representation of each vertex of is different, then the partition is called the resolving partition of , and the partition dimension is the smallest integer such that has a resolving partition with members. In this research, we show the partition dimensions of the cycle books graph . Cycle books graph is a graph consisting of copies of a cycle with a common path . The partition dimension of the cycle books graph for and is shown.